Chitosan-zinc oxide nanocomposite coatings for the prevention of marine biofouling. (February 2017) - Al-Naamani, Laila; Dobretsov, Sergey; Dutta, Joydeep; Burgess, J. Grant
Abstract: Marine biofouling is a worldwide problem affecting maritime industries. Global concerns about the high toxicity of antifouling paints have highlighted the need to develop less toxic antifouling coatings. Chitosan is a natural polymer with antimicrobial, antifungal and antialgal properties that is obtained from partial deacetylation of crustacean waste. In the present study, nanocomposite chitosan-zinc oxide (chitosan-ZnO) nanoparticle hybrid coatings were developed and their antifouling activity was tested. Chitosan-ZnO nanoparticle coatings showed anti-diatom activity against Navicula sp. and antibacterial activity against the marine bacterium Pseudoalteromonas nigrifaciens. Additional antifouling properties of the coatings were investigated in a mesocosm study using tanks containing natural sea water under controlled laboratory conditions. Each week for four weeks, biofilm was removed and analysed by flow cytometry to estimate total bacterial densities on the coated substrates. Chitosan-ZnO hybrid coatings led to better inhibition of bacterial growth in comparison to chitosan coatings alone, as determined by flow cytometry. This study demonstrates the antifouling potential of chitosan-ZnO nanocomposite hybrid coatings, which can be used for the prevention of biofouling. Graphical abstract: Highlights: Nanocomposite chitosan-ZnO nanoparticle hybrid coatings were developed. Incorporation of ZnO in the chitosan matrix improved physical characteristic of the coating. Chitosan-ZnO nanocomposite coatings showed high antidiatom and anti-bacterial activity. Chitosan-ZnO nanocomposite coatings represent a promising strategy for the prevention of biofouling.